(untitled) (International Journal of Physiotherapy, 2015)
Background: Asthma is an inflammatory clutter of the airways that causes wheezing, breathlessness, chest tightness, and coughing. In India, approximate calculation indicates a prevalence of between 10% and 15% in 5-11 year old children. Modern Western treatment focuses on controlling asthma with two classes of medication corticosteroids and bronchodilatorss. Another plan of action for reducing and potentially even throw out asthma manifestation affects manipulation of the craniosacral fascial system. This system is a unification of the craniosacral and fascial or connective tissue part. This idea can help in making clear the greatly high rate of achievement with manual therapy in pediatric asthma. Methods: In this case report first I have taken a brief history of the patient condition after the full assessment like brain cycle rhythm, chest and systemic. I have given cranio sacral therapy, Intercostal release, PNF for diaphragm release on child for seven sitting of about 45 minutes of each session. Results: After completion of treatment session of seven sitting his lungs to be bright of any wheezing or other impediment. Brain cycle was of 90 seconds. His peak flow meter readings were between 250 and 300 Liters/minute, which were in a satisfactory range for him. The physician suggested that at this point there was no requirement for any additional asthma medicines. Conclusion: It comes into sight that the loss to the respiratory system caused by fascial burden early in life may be fully reversible, if treated immediately. The latent grace of this interdependent approach is that it crop up to address the pathological origin of asthma.